Avaliação nutricional de pacientes submetidos à hemodiálise em Centros de Diálise de Belo Horizonte. - Glaucia Thaise Coimbra de Oliveira (2010)
Chronic renal failure is a progressive, debilitating and irreversible disease, which presents with high mortality. Hemodialysis is the most current used treatment. This therapy is associated with acute and chronic complications, high rates of hospitalization and increased mortality as well as with nutritional status derangements. Malnutrition, which is multifactorial, is widely prevalent among these patients and is considered a marker of poor prognosis. Therefore, it is necessary to characterize the nutritional status of hemodialysis patients, both to prevent malnutrition and to initiate appropriate intervention in malnourished patients. The present study aims at characterizing the nutritional status of patients undergoing hemodialysis in dialysis centers in the city of Belo Horizonte and associate it with demographic and socioeconomic variables as well as with those associated with the procedure per se. Five hundred and seventy five patients undergoing hemodialysis were assessed and the prevalence of malnutrition was significant (19.5%). This population presented, in general, with low socioeconomic status, decreased access to private health insurance, high levels of comorbidities and many of them had received a large number of nutritional recommendations, not necessarily adequate. Multivariate analysis showed that those who were elderly (> 60 years), as well as those with low income (below minimum salary), those with depression and those who were retired presented with increased risk of malnutrition.